Influence of cosmic radiation on bioorganic molecules and cells - Українська, А. О. (Problems of Environmental Biotechnology, 2018)
Effective space industry development and flight planning are impossible without a detailed study of the influence of cosmic radiation on the functioning of living organisms. The article is devoted to the search of information about the influence of cosmic rays on biologically active substances and cells of living organisms. The analysis of scientific data in the field of astrobiology concerning the influence of space rays on the functioning of living matter has been carried out.